Perivascular Epithelioid Cell Tumor in the Stomach - Sun Ah Shin; Jiwoon Choi; Kyung Chul Moon; Woo Ho Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Perivascular epithelioid cell tumors or PEComas can arise in any location in the body. However, a limited number of cases of gastric PEComa have been reported. We present two cases of gastric PEComas. The first case involved a 62-year-old woman who presented with a 4.2 cm gastric subepithelial mass in the prepyloric antrum, and the second case involved a 67-year-old man with a 5.0 cm mass slightly below the gastroesophageal junction. Microscopic examination revealed that both tumors were composed of perivascular epithelioid cells that were immunoreactive for melanocytic and smooth muscle markers. Prior to surgery, the clinical impression of both tumors was gastrointestinal stromal tumor (GIST), and the second case was erroneously diagnosed as GIST even after microscopic examination. Although gastric PEComa is a very rare neoplasm, it should be considered in the differential diagnosis of gastric submucosal lesions.